On the impact of labor market matching on regional disparities - Joe Tharakan; Jean-Philippe Tropeano (University College Dublin, Department of Economics, 2002)
We propose a model where imperfect matching between firms and workers on local labor markets leads to spatial agglomeration. We show that the occurrence of spatial agglomeration depends on initial size differences in terms of both number of workers and firms. We analyse the effect of different public policies. In our setting, the effect of a higher level of human capital on regional disparities depends on whether it makes workers more mobile on the labour market or more specialised. Policies that increase workers' interregional mobility, increase the likelihood that regions diverge. Finally, competition policy is shown to reduce regional disparities.
hdl:10197/1307
Keywords: J61; J42; R12; 330; Economic geography; local labor market; regional disparities; human capital; Regionaler Arbeitsmarkt; Regionale Disparität; Humankapital; Theorie